Biointensive management of blast disease of rice - CK, Yamini Varma; Santhakumari, P (ORYZA-An International Journal of Rice, 2021)
Blast of rice caused by Pyricularia grisea (Cooke.) Sacc. (Teleomorph :Magnaporthe oryzae) is a seriousÂ disease of rice and causes considerable reduction in yield. Overdose and untimely application of chemicalÂ fungicides disturb the rice ecosystem, pollute the environment and induce resistant mutants of the pathogen. AnÂ ecofriendly integrated disease management programme should be implemented to avoid overuse of a singleÂ control method and fight against genetic resistance. Salicylic acid (0.01ml/ l) and benzoic acid (0.01ml/ l)Â proved superior in inducing disease resistance among different inducers tested at Regional Agricultural ResearchÂ Station, Pattambi, Palakkad district of Kerala Agricultural University under green house conditions. As an integrated approach, palmarosa oil + carbendazim and palmarosa oil + salicylic acid were the most effectiveÂ treatments .Compatibility studies under in-vitro conditions showed that Trichoderma harzianum and FluorescentÂ pseudomonad were compatible with each other and also palmarosa oil and neemazal were compatible withÂ Trichoderma harzianum and Fluorescent pseudomonad. For the management of blast disease under fieldÂ conditions with high B:C ratio, Palmarosa oil (0.1%) + carbendazim (0.1%) was the best treatment followed by Trichoderma (2%) + Fluorescent pseudomonad (2%)+ palmarosa oil (0.1%).